EMERGENCY PREVENTION MEASURES - Kambarov Abduvali Xamidovich (Bright Mind Publishing, 2025)
This article aims to improve the existing system for the prevention of emergency situations related to floods and landslides in Uzbekistan, to increase its efficiency using the possibilities of modern information technologies based on innovative approaches, to protect the life and health of the population from possible emergency situations.
Keywords: Floods, floods, inundation, material losses, danger, human casualties, damage to the natural environment, destruction.